BUILDING A SUPERIOR SCHOOL IDENTITY: THE ROLE OF TRANSFORMATIONAL LEADERSHIP AND TEACHER COMPETENCE IN STRENGTHENING SCHOOL BRANDING - Muhammad Adelin (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
In an era of increasingly competitive education, schools are not only required to excel academically but also to have a strong image and identity in the community. This study used a literature review method. The results of relevant research discuss the relationship between leadership, teacher competency, and school branding strategies. The study shows that the principal's transformational leadership plays a crucial role in creating a vision and organizational culture that supports the strengthening of school identity. A visionary, inspiring, and participatory principal can increase teacher motivation and build a positive and innovative school climate. Meanwhile, teacher competency has a direct influence on the effectiveness of school branding, as teachers represent the school's values, quality, and character in the eyes of the community. Teachers who are professional, creative, and possess communication skills and mastery of information technology can significantly enhance a school's positive image.